Research on the Development of Computer Communication and Networks in the New Era - Wang, Yao; Wang, Haoyu (Journal of Theory and Practice of Management Science, 2025)
Currently, modern information technology has been widely applied in various industries, and computers are becoming an effective tool for people's learning, life, and work.At this stage, we have entered the Internet era, and the computer communication technology has gradually developed rapidly, which has laid a solid foundation for China's informatization construction. The effective promotion of China's computer communication network technology can further enhance China's comprehensive national strength.Network communication technology has made people's lifestyles more convenient. Remote video through computers and communication through email have gradually become important ways for people to interact and communicate online.Computers have enabled people from different regions to no longer be limited by time and space. They can achieve sharing through network resources and use information technology to process relevant communication information at high speed. This new way of communication has brought great convenience to people's learning, life, and work, saving them a lot of time.Therefore, effectively applying computer communication technology, promoting network development, and achieving the goal of rapid data transmission can further promote the rapid development of China's economy.